Visual Diagnosis of Pleural Tuberculosis and its Association with Tissue Biopsy, Culture and Xpert Assay - Sumalani, Kamran Khan; Akhter, Nousheen; Chawla, Dimple; Rizvi, Nadeem Ahmed (Pneumologie, 2021)
Introduction The diagnosis of pleural tuberculosis remains a clinical challenge due to the paucibacillary nature of disease. Medical thoracoscopy remains the gold standard in diagnosing tuberculous pleuritis.Objective To establish the diagnostic yield of sago-seed thoracoscopic appearance of pleura in tuberculosis and its correlation with histopathology, tissue AFB culture and tissue Xpert MTB/Rif assay.Methods All consecutive patients with lymphocytic exudative pleural effusion, who fulfilled inclusion criteria of the study underwent medical thoracoscopy under local anesthesia and pleural tissue was sent for histopathology, AFB culture and Xpert MTB/Rif assay. Chronic granulomatous inflammation on histopathology and response to anti-tuberculous treatment was taken as reference standard for diagnosis of tuberculous pleurisy.Results A total of 249 patients were included in the study, out of which 168 had effusion secondary to tuberculosis. Sago-like nodules visualized on thoracoscopy had a sensitivity of 58.9 %, specificity of 92.6 % and diagnostic accuracy of 69.88 % for pleural tuberculosis. There is a strong association between the presence of sago-like nodules and detection of mycobacterium tuberculosis on Xpert MTB/Rif assay and AFB culture of pleura (p-value 0.007).Conclusion Sago seed nodules on pleura have a high positive predictive value for tuberculous pleurisy. In high endemic countries patients with this finding on thoracoscopy can be commenced on anti-tuberculous treatment before histopathology or culture results are available.